(untitled) (Scientific journal of the Fergana State University, 2024)
This article reveals the growing importance of national and universal values in human life and society, their role in the development of youth. Education comes to the fore in determining the essence of every person’s life. Education plays a very important role in shaping a person’s worldview, in learning the secrets of life, in finding one’s place in life, in other words, in becoming a person as a part of the society in which he lives - as a human being. The article also reveals the need to implement the development strategy of New Uzbekistan, based on national and universal values.